Cytokinin biosynthesis in cyanobacteria: Insights for crop improvement - Uniyal, Shashi; Bhandari, Munni; Singh, Preeti; Singh, Rahul Kunwar; Tiwari, Shree Prakash (Frontiers in Genetics, 2022)
Cytokinins, a type of phytohormone that induce division of cytoplasm, have considerable value in agriculture due to its influences on several physiological processes of plants such as morphogenesis, development of chloroplast, seed dormancy, leaf senescence etc. Previously, it was assumed that plants obtain cytokinin from soil produced by microbes as these hormones were first discovered in soil inhabiting bacteria i.e., Agrobacterium tumefaciens. Later, cytokinin biosynthesis gene, i.e. ipt gene, have been reported in plants too. Though plants synthesize cytokinins, several studies have reported that exogenous application of cytokinins have numerous beneficial effects including acceleration of plant growth and boosting economic yield. Cyanobacteria may be employed in the soil not only as the source of cytokinins but also as the source of other plant growth promoting metabolites. These organisms biosynthesize the cytokinins using the enzyme isopentynyl transferases (IPT) in a fashion similar to the plants. However, there are few differences in biosynthesis mechanism of cytokinins in cyanobacteria and plants. Cytokinins are important for establishment of interaction between plants and cyanobacteria as evidenced by gene knockout experiments. These hormones are also helpful in alleviating the adverse effect of abiotic stresses on plant development. Cyanobacterial supplements in the field result in induction of adventitious roots and shoots on petiolar as well as intermodal segments. The leaf, root and stem explants of certain plants, exhibited successful regeneration when treated with cyanobacterial extract/ cell suspension. These successful regeneration practices mark the way of cyanobacterial deployment in the field as a great move towards the goal of sustainable agriculture.